2018
DOI: 10.1021/acs.jpca.8b05612
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Vibrational Hyperpolarizabilities of Lithium Substituted (Aza)benzenes and (Aza)naphthalenes

Abstract: In this article we report results for the electronic and vibrational hyperpolarizabilities of ten molecules: Li@benzene, Li@pyridine, Li@pyrimidine, and Li@pyrazine; Li@naphthalene, Li@quinoline, Li@isoquinoline, Li@cinnolin, Li@quinazoline, and Li@quinoxaline. An electron correlation study shows that second-order many-body perturbation theory and density functional theory with CAM-B3LYP and M05-2X functionals give results for the electronic hyperpolarizabilities in good agreement with coupled cluster with sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…frequencies higher than 300 cm −1 , indicating that the BKPT method is suitable for treating these effects. [55] An exception among the systems shown in Figure 3 is K@B-BNNT, whose mode giving the largest contribution has a frequency of 137 cm −1 . It is possible that its contribution is somewhat overestimated.…”
Section: Computational Detailsmentioning
confidence: 93%
See 4 more Smart Citations
“…frequencies higher than 300 cm −1 , indicating that the BKPT method is suitable for treating these effects. [55] An exception among the systems shown in Figure 3 is K@B-BNNT, whose mode giving the largest contribution has a frequency of 137 cm −1 . It is possible that its contribution is somewhat overestimated.…”
Section: Computational Detailsmentioning
confidence: 93%
“…In this article, we did not calculate the zpva correction for two reasons: (a) the calculation of this property is computationally more expensive because it involves calculations of the first and second derivatives of the β components and (b) previous works show that in general the zpva correction is smaller than the electronic contribution and even the pv correction. [55][56][57][58] The calculation of the [μα] 0,0 harmonic term is more accessible because it requires only the computation of the first derivatives of the dipole moment and polarizability components. On the other hand, the [μ 3 ] 1,0 and [μ 3 ] 0,1 anharmonic terms were calculated by means of the field-induced coordinates methodology (FIC) of Luis et al [59] It was shown that, at the limits ω !…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations